Impact of cross-listing on the United States and the United Kingdom on the firm value: Evidence from Chinese and Japanese companies - Nguyen, Thi Anh (2018)
This dissertation scrutinizes existence of cross-listing premium for Chinese and Japanese stocks which are listed on US or UK stock exchanges. Tobin’s Q is used as proxy for firm’s valuation. Applying Random effects model on 1084 year-observations of 46 cross-listed and 90 non-cross-listed companies in the two countries over the period 2010-2017, the study identifies a positive premium on both listing destinations. However, there is a statistically significant premium of UK cross-listing on firm’s valuation. The US cross-listing premium differs substantially among Chinese and Japanese enterprises. While Japanese companies listed on US exchanges command a positive premium, the US listing decision affects negatively corporate value of Chinese corporations. It suggests the impacts of legal requirement changes in listing destinations and home country characteristics on firm’s value. Additionally, three control variables including Firm size, Median Tobin’s Q of sector and Country-level liquidity have significant effects on Tobin’s Q, while Cash holding, Sales growth and Sovereign governance affects little Tobin’s Q. To check for robustness, the study applies two-step treatment effects method and the evidence of premium is consistent. Furthermore, coefficients of interaction variables indicate that companies with great opportunities and from better sovereign governance countries benefit more after cross-listing decision.